AN ANALYSIS OF FLOUTING THE MAXIMS IN FOODVENDORS' UTTERANCES - Lia Marlia, - (2009)
The present study is entitled An Analysis of Flouting the Maxims in Food Vendors' Utterances. The purpose of this study is to analyze the flouts of maxims and speech functions of their non-observance the maxims which occurred in food vendors' utterances. This study uses a qualitative method and the subjects of the study were three food vendors who were selling their products around the researcher's house. The data were obtained through recording and transcribing the food vendors' utterances. The collected data were analyzed by using the theory of Grice's Conversational Maxims (1989) and Hallidayan theory (1985). The analysis focuses on the vendors' utterances. The result of the study shows that all the food vendors flouted the maxims and all types of speech functions occurred in their utterances. It was found that the maxim of quantity tended to appear frequently in the food vendors' utterances with 39 occurrences (36.8%). Thus, it seems that the maxim of quantity was dominant in their utterances. And the lowest number of occurrences was the maxim of quality with 10 occurrences (9.4%). Based on the analysis results, the flouting of maxims was identified through six manners. Those were giving more information, less information, unnecessary prolixity, obscure utterances, false facts and irrelevant answer. The highest percentage appeared in giving more information (35.4%) and the lowest percentage occurred in giving false facts (3%). Meanwhile, the other manners of flouting the maxims were on average. The analysis also reveals that the speech function of their non-observance the maxims that mostly occurred in the food vendors' utterances was a statement (53.5%). It was followed by an offer (23.3%), a question (18.9%), and a command (4.3%). Finally, it can be concluded that Conversational Maxims were not found in the food vendors' utterances and they used speech functions in communicating with their costumers.